127k views
1 vote
Simplify the expression below. (-3x2 + 2x - 4) + (4x2 + 5x +9)

2 Answers

7 votes

Answer:

x^2+7x+5

Explanation:

Remove parentheses: -3x^2+2x-4+4x^2+5x+9

Group like terms: -3x^2+4x^2+2x+5x-4+9

Add similar elements: x^2+2x+5x-4+9

Add/subtract the numbers: x^2+7x+5

User TheEsnSiavashi
by
4.7k points
4 votes

Answer: =x2+7x+5

Step-by-step explanation:

−3x2+2x−4+4x2+5x+9

=−3x2+2x+−4+4x2+5x+9

Combine Like Terms:

=−3x2+2x+−4+4x2+5x+9

=(−3x2+4x2)+(2x+5x)+(−4+9)

=x2+7x+5

Answer:

=x2+7x+5

User Kevin Stone
by
5.8k points